Tatwir Wasilah Ta’lim Fii qismi At-ta’lim Al-lughah Al-Arabiyah Bi Isti’mal Airsite - Prayoga Saputra (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
Now, the evolution of time is known as the technological and digital age. The main issue in this thesis is how to develop the teaching method in the Arabic language department using Airsite? The desired objectives of this research are: To describe the needs analysis, design and development of the teaching method in the Department of Teaching Arabic using Airsite. As for the two inputs used in this research, they are the qualitative approach and the quantitative one on the method of research and development in the 4D model, consisting of definition, design, development and dissemination. However, the researcher determined the research procedures for development in terms of expert arbitration in terms of the means. As for collecting data for research and development, by multiple means, including: documents, questionnaire, interview, and expert arbitration (in terms of the means) with notes and additions from experts. As for the results of the development research, they are: Analyzing the needs of the Arabic language teacher and analyzing the needs of the students indicates that the teacher and students need to be developed. The design of the teaching method consists of: collecting materials and making materials for the design of teaching Arabic language. As for the development of the teaching method, it consists of: certification of expert arbitration on the one hand. The means, product modification, and final production. Based on the development results, expert arbitration approval, and product experience, Airsite was very suitable to be used as an Arabic language teaching tool for a special Arabic language teaching design